2019
DOI: 10.2147/ppa.s187080
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations of different adherences in patients with type 2 diabetes mellitus</p>

Abstract: PurposeThe objective of our cross-sectional study is to explore the adherence behavior of patients with type 2 diabetes mellitus (T2DM) by examining the association between the various types of adherence. The success of diabetic therapy partly relies on patient motivation, psych-odemographic variables (self-efficacy, health literacy, and health locus of control [HLOC]), and adherence. The aim of our research was to explore the attitudes of T2DM patients toward medication and lifestyle therapy, thus gaining a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
5
15
0
4
Order By: Relevance
“…The results of research carried out by Basińska et al, in which the respondents placed the strongest health locus of control in the internal dimension, and the weakest in the chance [13], are different. Similar results were presented in the research conducted by Klinovszky et al, where the respondents most strongly indicated the important role of internal health control; secondly, they located health control in other people, and lastly in chance [14].…”
Section: Discussionsupporting
confidence: 88%
“…The results of research carried out by Basińska et al, in which the respondents placed the strongest health locus of control in the internal dimension, and the weakest in the chance [13], are different. Similar results were presented in the research conducted by Klinovszky et al, where the respondents most strongly indicated the important role of internal health control; secondly, they located health control in other people, and lastly in chance [14].…”
Section: Discussionsupporting
confidence: 88%
“…Effective self‐management is essential to prevent diabetes‐associated complications and includes significant lifestyle changes related to diet, activity and monitoring (American Association of Diabetes Educators, 2014). Individuals’ adherence to such changes varies with their perceived health locus of control, diabetes self‐efficacy and length of time with their type 2 diabetes diagnosis (Klinovszky, Kiss, Papp‐Zipernovszky, Lengyel, & Buzás, 2019). Facilitators and barriers to effective diabetes self‐management behaviours vary among individuals and can change over time (Harvey, Dopson, McManus, & Powell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Patient–physician relationship and family support also play the major role in patients’ self-care adherence.14 Some studies have reported that self-efficacy and positive attitude also can minimize the barriers to self-care adherence towards management of diabetes 14,15. Health belief and patient attitude towards management of diabetes may be affected by inadequate knowledge about diabetes, inability to understand doctor’s instruction and fear on the side effect of long-term medication.16 Alongside, improvement on self-care adherence and minimization of their barriers can be achieved by focusing on diabetic education and self-management support programs to the specific population.15…”
Section: Introductionmentioning
confidence: 99%